Neurotoxicity of Uranyl Acetate in Male Rats - Aziz, Falah M.; Ismael, Nadhum J. (Science Journal of University of Zakho, 2013)
The present investigation included the neurotoxic effect of different doses of uranyl acetate in male rats. Routine light and electron microscopic techniques were used in this study. The histological studies of cerebellum and cerebrum showed a significant increase of died and decrease of healthy pyramidal cells in the 3rd layer of cerebrum and Purkinje cells in the cerebellum. This may indicate the passage of uranium across the blood brain barrier or disruption of this barrier due to uranium exposure..
Keywords: Cerebellum; Cerebrum; Purkinje cells; uranyl acetate